Jahresgaben 1995 : Neuer Aachener Kunstverein. - NAK (Neuer Aachener Kunstverein), Aachen (Aachen : Neuer Aachener Kunstverein, 1995)
Bernstein, Ron ; Demary, Stefan ; Drescher, Jürgen ; Droese, Felix ; Hahn, Wolfgang ; Kohl, Thomas ; von Lintig, Sigrid ; Nagel, Peter ; Schrey, Anja ; Sous, Vera ; Virnich, Thomas ; Wurm, Erwin
Duits
boek